2017
DOI: 10.1016/j.ultsonch.2017.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound assisted phytosynthesis of iron oxide nanoparticle

Abstract: The present work deals with the ultrasound assisted green synthesis of iron oxide nano particle using Coriandrum sativum leaf extract as a reducing agent. The synthesized iron oxide nanoparticle was confirmed by UV spectra. The characterization was done to know more about morphology and size of the particle by SEM analysis which shows spherical particles with size ranging from 20 to 90nm. The antimicrobial activity of the leaf extract and the synthesized nanoparticles was studied against the pathogens Micrococ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…The phase structure of obtained materials was identified with XRD using X’Pert Pro Philips camera using an X-ray lamp with a copper anode emitting CuK α radiation. The average crystallite size of magnetite and anatase was determined with the Scherrer Equation (5) [ 44 ]: where D—crystallite size, k—shape factor, λ—X-ray wavelength, β—full width at half the maximum, and θ—Braggs’ angle.…”
Section: Methodsmentioning
confidence: 99%
“…The phase structure of obtained materials was identified with XRD using X’Pert Pro Philips camera using an X-ray lamp with a copper anode emitting CuK α radiation. The average crystallite size of magnetite and anatase was determined with the Scherrer Equation (5) [ 44 ]: where D—crystallite size, k—shape factor, λ—X-ray wavelength, β—full width at half the maximum, and θ—Braggs’ angle.…”
Section: Methodsmentioning
confidence: 99%
“…The pH of the mixture was adjusted with Na 2 CO 3 to indicate colour change on formation of nanoparticles. Sathya et al (2017a) have reported the synthesis of iron oxide nanoparticles from the leaves of Coriandrum sativum using ferric chloride as the precursor. Spherical nanoparticles with size ranging from 20−90 nm was prepared and characterized using FTIR, SEM with EDX.…”
Section: Plant-mediated Synthesismentioning
confidence: 99%
“…Duing the preparation Fe 3 O 4 NPs, the conical flask containing 50 ml of ferric chloride hexahydrate (0.2 M) was added to 0.001, 0.01, and 0.1 M concentrations of FeCl 2 .4H 2 O (50 ml) under stirring on a magnetic stirrer for 2 h. Afterward, 10 mL of the aqueous extract of A. haussknechtii leaves was mixed with 90 ml of resulted solution and pH is adjusted to 8, by the addition of 0.1 M NaOH solution. The above reaction was under a stirring condition at room temperature followed by the application of ultrasonic irradiation for 2 h with a frequency of 40 kHz and the total acoustic power of 50 W [30]. In comparison analysis, the effect of different temperatures (4,25,35,45,55, and 65 C) on MNPs synthesis was measured in the range of 1-7 h. In order to purify MNPs, the resulting solution was centrifuged at 4000 rpm for 5 Â 10 min and washed several times with 1:1 mixture of absolute methanol and distilled water.…”
Section: Leaves Extract Preparation and Biosynthesis Of Fe 3 O 4 Npsmentioning
confidence: 99%